Design Concept of Mixed Use Building Connection Bridge of Al Amin Living Lab and Industrial Park Main Plaza at Desa Sampe Cita, Kutalimbaru - Dara Wisdianti; Novalinda Novalinda; Faurantia Forlana Sigit; Ida Khairani Siregar (International Journal of Mechanical, Electrical and Civil Engineering, 2024)
Universitas Pembangunan Panca Budi plans to develop Al-Amin Living Lab and Industrial Park. In the center of this area is the main plaza which has a series of mixed use buildings that need to be connected. This study aims to understand the design of the connection bridge at the main plaza of Al-Amin Living Lab and Industrial Park in Sampe Cita Village, Kutalimbaru District, and how it will serve pedestrians. The research subject is the site location in Sampe Cita Village, Kutalimbaru District, Deli Serdang Regency, with the observed parameters being the physical and non-physical conditions of the design location. The results of this study show that the facilities and infrastructure of the connection bridge for the Mixed-Use Building of Al-Amin Living Lab and Industrial Park consist of circulation pathways connecting the Mixed-Use buildings and a viewing deck, and the design direction of the Mixed- Use Building of Al-Amin Living Lab and Industrial Park meets the criteria.